Advanced Learning and Teaching Environments Innovation, Contents and Methods - Llevot-Calvet, Núria; Bernad Cavero, Olga (IntechOpen, 2018)
In a plural, complex, and diverse society, the school faces many challenges. Teachers must prepare their students for future professions, unthinkable nowadays, and the digital competences of teachers and students are one of the axes of an advanced school. This book presents a set of works rigorously elaborated by authors of different disciplines, on the role of information and communication technologies (ICT) in educational centers and on the use of digital resources in the initial and continuing teacher training to improve them, as well as in the teaching of different subjects to achieve a better academic and social performance of students. Besides, the reader will find some innovative experiences in physical education to achieve a better physical, emotional, and social performance of students.